Enhancing Vocabulary Among EFL Young Learners Through Picture-Word Inductive Model - Hamdani, Beny (Universitas Nurul Jadid, 2020)
AbstractThis paper critically aims to enhance English vocabularies among EFL young learners of the fifth grade students through picture-word inductive model at elementary school Zainul Hasan Genggong Probolinggo in the academic year of 2019-2020. The research problem is How is the effective picture-word inductive model to enhance vocabulary among young learners of elemantary school Zainul Hasan Genggong Probolinggo? The type of the research is classroom action research. It was conducted in two cycles. The subjects of the research were 20 students of fifth grade. The data were collected from the test, interview, documentation and observation. The result showed that the students had increased their English vocabulary mastery which can be seen from the test result provided by the researcher. This is the evident from the test result that overall there was an increase in the English vocabulary mastery of 5 grade students as much as 50.70 % in the first cycle and 85.54 % in the second cycle. Meanwhile, the observation result showed that the students seemed more enthusiastic during the learning process.Â In reference to the actions conducted in two cycles, the use of the picture-word inductive model enhances the studentsâ€™ vocabulary by practicing words into sentences and more attention on mechanical aspects such as spelling and pronunciation.Â Keywords : Young Learners, Vocabulary Mastery, Picture-word inductive model.